Understanding practical challenges to risk and vulnerability assessments: the case of Swedish municipalities. Issue 6 (3rd June 2019) - Cedergren, Alexander; Hedtjärn Swaling, Vidar; Hassel, Henrik; Denward, Carl; Mossberg Sonnek, Karin; Albinsson, Pär-Anders; Bengtsson, Johan; Sparf, Anna
Abstract: Assessing risks and vulnerabilities in the multifaceted context of a municipality is challenging. There is a plethora of methods and tools to support this task. However, to achieve successful outcomes from Risk and Vulnerability Assessments (RVAs), merely applying theoretically and technically rigorous methods is far from enough; the question of how a method is implemented in a practical context is crucial for reaching intended outcomes. In this paper, we broaden the scope, from a strict consideration of technical and methodological matters, to a presentation of the more elusive challenges in accomplishing RVAs that are actually useful in a local context. We conduct and contrast two independent studies that were aimed at identifying general challenges in achieving a successful RVA process in Swedish municipalities. Based on the findings, we argue that there is a need for a considerably increased focus on municipal practices and on the implementation of methods in the practical context. Knowledge and understanding of such practical challenges are pivotal for efforts aimed at both developing methods for RVA and improving the entire RVA process.